2020
DOI: 10.1111/cas.14686
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial pneumonitis related to trastuzumab deruxtecan, a human epidermal growth factor receptor 2‐targeting Ab–drug conjugate, in monkeys

Abstract: Trastuzumab deruxtecan (T‐DXd: DS‐8201a) is an anti‐human epidermal growth factor receptor 2 (HER2) Ab–drug conjugated with deruxtecan (DXd), a derivative of exatecan. The objective of this study was to characterize T‐DXd‐induced lung toxicity in cynomolgus monkeys. Trastuzumab deruxtecan was injected i.v. into monkeys once every 3 weeks for 6 weeks (10, 30, and 78.8 mg/kg) or for 3 months (3, 10, and 30 mg/kg). To evaluate the involvement of DXd alone in T‐DXd‐induced toxicity, DXd monohydrate was given i.v. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 33 publications
5
48
0
Order By: Relevance
“…The mechanism by which T-DXd is involved in the development of ILD is currently unknown. Preclinical studies in monkeys found that high level of T-DXd exposure resulted in the development of a similar pathology to what was observed in the treatment-associated ILD/ pneumonitis in humans [43]. In this model, T-DXd was detected in HER2-negative lung alveolar macrophages, but not in the airway epithelium including HER2-positive bronchial and bronchiolar epithelial cells.…”
Section: Interstitial Lung Diseasesupporting
confidence: 64%
“…The mechanism by which T-DXd is involved in the development of ILD is currently unknown. Preclinical studies in monkeys found that high level of T-DXd exposure resulted in the development of a similar pathology to what was observed in the treatment-associated ILD/ pneumonitis in humans [43]. In this model, T-DXd was detected in HER2-negative lung alveolar macrophages, but not in the airway epithelium including HER2-positive bronchial and bronchiolar epithelial cells.…”
Section: Interstitial Lung Diseasesupporting
confidence: 64%
“…An in vivo study conducted in cynomolgus monkeys injected with T-DXd at different doses revealed histopathological lung features of diffuse lymphocytic infiltrates and slight fibrosis with an incidence that was dose-dependent and dose-frequency-dependent. Immunohistochemical analysis further confirmed that T-DXd localization was mainly in alveolar macrophages, but not pulmonary epithelial cells suggesting a possible mechanism of lung injury related to target-independent uptake of T-DXd into alveolar macrophages [47]. Additional work will be necessary to clarify these findings and their clinical implications.…”
Section: Toxicity Profilementioning
confidence: 82%
“…Receiving T-Dxd in a monkey model developed interstitial lung disease, whereas receiving Dxd does not. Although most ILD lesions were found within the alveoli, the HER2 expression in lungs was limited to the bronchial level [ 22 ]. Vasculitis due to a pathway via ANCA autoantibodies, an indirect mechanism by the immune system, could explain why the injury was not at the location where T-Dxd was uptaken.…”
Section: Discussionmentioning
confidence: 99%